Foodomics of Rice Grains in Astrobiology: Spaceflight-Induced Modulation of Aroma, Texture, and Protein Digestibility in Thai Landrace Rice (466HM) Aboard the Shijian-19 (SJ-19) Low Earth Orbit Mission - Tatpong Tulyananda; Yodying Yingchutrakul; Kakanang Tantraphongsathon; Atiggamas Khamsuwan; Peerapon Moung-Ngam; Phanchita Vejchasarn; Phakorn Papan; Jakkaphan Kumsab; Chutikarn Butkinaree; Sithichoke Tangphatsornruang; Meng Chieh Yang; Arnatchai Maiuthed; et al. (Life, 2026)
> 0.05), alongside distinct alterations in flavor-related volatile compounds and peptide profiles. Principal component analysis revealed clear separation between Earth and LEO-exposed samples, indicating microgravity-associated shifts in digestible peptide composition. Cytotoxicity assessment using MTT assays in HT-29 and HepG2 cells confirmed the safety of both rice types. These findings demonstrate that orbital conditions influence the compositional, functional, and sensory attributes of rice, providing insights relevant to space agriculture and astronaut nutrition.
Keywords: Spaceflight effects on biology; Light effects on plants; Genetics, Aging, and Longevity in Model Organisms